Impact of Cooling Profile on Refined Palm Oil Crystallization: Microscopic and Small and Wide‐Angle X‐Ray Scattering Investigations. Issue 2 (28th November 2021) - Sainlaud, Chloé; Taché, Olivier; Testard, Fabienne; Saiter, Jean‐Marc; Bohin, Maxime C.; Coquerel, Gérard
Abstract: Among the different possible strategies, thermal control is a major lever to control fat structure (i.e., triacylglycerols (TAGs) molecules organization and crystals morphology). In this article, the impact of thermal treatments on TAGs packing tendency contained in refined palm oil (RPO) is determined. Three cooling profiles are considered: slow, intermediate, and fast. Slow cooling induces the formation of β' polymorphic form in sequence as 2Lβ' then 3Lβ' configurations. RPO rapidly cooled first crystallizes in α form before turning into the 2Lβ' structure. At intermediate cooling profile, 2Lβ' and 3Lβ' are observed and another original phase ϕ is formed around 0°C. This phase has similarities with the sub‐α phase observed in cocoa butter which corresponds to a β' subcell and presents the capacity of adapting its composition during cooling, leading to an increase of its interplanar distances by decreasing temperature. Practical applications : In case of fats in food products, suitable cooling profile is a compromise between rheological properties of final product (thus, sensorial properties) and relative stability during storage. In this article, three different cooling profiles applied to RPO, leading to various crystal lattices are studied. These lead to systems with varying sensory properties and stability. Abstract : A variation of cooling profiles induces differences in terms of micro‐ and nanostructure of crystallized refined palm oil (RPO). An original phase ϕ is observed by small‐angle X‐ray scattering analysis during intermediate cooling of RPO. This phase presents the particularity to adapt its composition with temperature (increase of interplanar distances with cooling) and presents some similarities with the sub‐α form observed in cocoa butter.